Mechanisms underlying apathy in health and Parkinson's disease - Muhammed, K (2018)
Apathy or lack of motivation is increasingly recognized to be a major factor affecting quality of life and prognosis in many neurological conditions. It is particularly prevalent in Parkinson’s disease, impacting on every disease stage, including de novo cases, and has been reported to affect up to 70% of cases. Despite the pervasiveness of apathy, challenges remain in its detection, clinical assessment and treatment. Several lines of evidence have implicated fronto-striatal reward related neural pathways in the genesis of apathy but the precise processes remain to be fully explained. This thesis examines the potential mechanisms of apathy using Parkinson’s disease as a model to study the condition. Novel oculomotor tasks that used eye movement and pupillary responses were developed to help assess if insensitivity to incentives could be an underlying component of apathy. This was examined in healthy young and elderly participants as well as in patients with Parkinson’s disease. Patients were tested both ON and OFF their normal dopaminergic medication so that the effect of dopamine could be assessed and the association with apathy determined. This was also performed in a pharmacological study in young participants with the use of Haloperidol, a dopaminergic D2-selective antagonist. Insensitivity to rewards modulated by dopamine was regarded to be a contributory mechanism of apathy in Parkinson’s disease and also applicable to general mechanisms of motivation in healthy populations.